Analysis of the Palestinian and Israeli Conflict in the Perspective of International Humanitarian Law - Mahwati, Tri; Nanda, Ana Risma (Faculty of Law, Universitas Negeri Semarang, 2022)
The conflict between Israel and Palestine to this day continues. Many studies even reveal that the conflict between Israel and Palestine is not only related to religious ideology and belief but also related to legal aspects, especially international law. This study aims to analyze the Israeli-Palestinian conflict from the point of view of International Humanitarian Law. This study finds and confirms that International Humanitarian Law can be used optimally in providing protection for civilians in times of armed conflict. However, several other related studies found that there were many violations of human rights in Palestine by the Israeli army, especially against civilians. This of course violates basic conventions on human rights and other rules of international law.